A Multimedia Option for Delivering Feedback and Professional Development to Teachers. Issue 2 (June 2022) - Kunemund, Rachel L.; Kennedy, Michael J.; Griendling, Lindsay M.; VanUitert, Victoria J.; McDonald, Sean D.
All teachers need ongoing coaching that helps them recognize areas of strength and need for teaching students with disabilities. Unfortunately, the amount, quality, and speed with which teachers receive feedback from coaches, administrators, mentors, or other instructional leaders on their academic and behavior management practices is limited. In this article, we describe a multimedia professional development option for documenting teacher practice, generating feedback, and delivering targeted instruction.